Social justice in islam: the perspective of Tjokroaminoto & Syed Hussein Alatas - Juliyana Junaidi,; Latifah Abdul Majid,; Mohd Arif Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2023)
With the rapid invention of technology, the twenty-first century allows us to witness social injustice issues across the globe via our own electronic devices. These issues lead to the collapse of morality, hence destructing the societal fabric. Social justice discourse has been in existence since World War 2, yet most literature available pays more attention to the social justice issues from the western perspective than the views of the Muslim scholars, especially those of Malay Archipelago. Therefore, this study aims to unfold the principles of social justice according to Tjokroaminoto and Syed Hussein Alatas, and to identify the similarities and differences of views on social justice between these two figures. This qualitative study utilised document analysis whereby both of their books with the same title, “Islam dan Sosialisme” were used to analyse the principles, similarities, and differences of ideas on social justice. The findings demonstrate that both figures are among the proponents of socialism in Islam which covers the idea of social justice despite the idea being rejected by some Muslim scholars from Arabia and India subcontinents. Both figures presented the proof that socialism has its foundation in the divine revelation, and the implementation of social justice was manifested by Prophet Muhammad PBUH as the guided individual in Islam.